Effect of Different Genotypes and Harvest Times of Sage (Salvia spp. Labiatae) on Lipid Oxidation of Cooked Meat - Kathrine H. Bak; Susanne Bauer; Friedrich Bauer (MDPI AG, 2023)
Lipid oxidation is the primary non-microbial reason for quality deterioration of meat and meat products. Lipid oxidation can be prevented or delayed by antioxidants. In this study, 15 sage (Salvia spp. Labiatae) extracts (five genotypes, three harvest times) were tested for their ability to reduce lipid oxidation (peroxide value (PV) and thiobarbituric acid reactive substances (TBARS)) in ground, uncured, cooked porcine and bovine meat (60%/40% mixture) during 14 days of refrigerated storage. Additionally, total phenolic content was determined, and the antioxidant capacity of the extracts was measured as radical scavenging activity (2,2-diphenyl-1-picrylhydrazyl assay), reducing power, and superoxide anion scavenging activity. All 15 sage extracts were able to reduce lipid oxidation, though showing expected differences depending on genotype and harvest time. The extracts of S. officinalis accession from Foggia, Italy performed better than the other genotypes when looking at the entire storage period and considering both PV and TBARS. Of the applied methods for determining antioxidant capacity, superoxide anion scavenging activity proved to be the best determinant of the ability of sage to reduce lipid oxidation in the meat sample.